Communication and Interaction as Key Aspects of Personal Learning Environments: Perspectives of Costa Rican Education Students - García-Martínez, José Antonio (2020)
Thanks to the proliferation of new information and communication technologies, and through increasingly global internet access, significant changes are being made in both the way we work in the classroom and in the relationships generated by the educational community; this calls for further development of communicative skills as key components of personal learning environments (PLE). This research aims to analyze the tools that Costa Rican education students know and use; it also examines the activities and mechanisms the students generate with their use to promote the communication processes to different levels. From a quantitative approach, and under a non-experimental design, information from a sample of 421 students is collected through a questionnaire composed of different scales. The main tools used to share information are social networks, email, and mobile apps; other resources are largely unknown. The main activities are linked to sending emails, communicating through chat applications, and using the Learning Management System (LMS). The vast majority of students (41.7%) indicate that they use the tools to share information and learn from others; although, it is worth highlighting that a high percentage (20%) does not use them for any of the options mentioned. It is necessary and urgent to stimulate and enrich students’ PLEs so that they can make the most of the resources available to facilitate their learning and develop their communication skills.